2015
DOI: 10.1038/eye.2015.87
|View full text |Cite
|
Sign up to set email alerts
|

Transitioning to intravitreal aflibercept following a previous treat-and-extend dosing regimen in neovascular age-related macular degeneration: 24-month results

Abstract: Purpose: To evaluate frequency of injections, visual and anatomical outcomes of neovascular age-related macular degeneration (nAMD) patients transitioned to intravitreal aflibercept after failure to extend treatment interval beyond 8 weeks with prior intravitreal bevacizumab or ranibizumab. Methods: Retrospective review of patients with nAMD switched to aflibercept following ≥ 6 prior intravitreal ranibizumab or bevacizumab injections at 4-8-week intervals. Three monthly aflibercept injections were given follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 8 publications
3
17
0
1
Order By: Relevance
“…Our results are in accordance with studies investigating both the outcome after switching from ranibizumab and/or bevacizumab to aflibercept [3, 814, 18] and after switching from bevacizumab to ranibizumab [5, 15, 16]. Fassnacht-Riederle et al only found minimal functional improvement when switching to aflibercept after initial treatment with ranibizumab and/or bevacizumab: Visual acuity increased about 1.8 letters in ETDRS visual acuity score but did not reach statistical significance [3].…”
Section: Discussionsupporting
confidence: 92%
“…Our results are in accordance with studies investigating both the outcome after switching from ranibizumab and/or bevacizumab to aflibercept [3, 814, 18] and after switching from bevacizumab to ranibizumab [5, 15, 16]. Fassnacht-Riederle et al only found minimal functional improvement when switching to aflibercept after initial treatment with ranibizumab and/or bevacizumab: Visual acuity increased about 1.8 letters in ETDRS visual acuity score but did not reach statistical significance [3].…”
Section: Discussionsupporting
confidence: 92%
“…; Homer et al. ). There are several adverse events and complications associated with intravitreal injections (Falavarjani & Nguyen ), of which some are clearly correlated to the number of injections while others may be related to the type of medication being injected.…”
Section: Introductionmentioning
confidence: 97%
“…However; CMT improvement was found to be showed a significant improvement in both visual and anatomical outcomes in switched eyes. Conversely, Homer et al [24] did not report an improvement but a maintanance in macular thickness and visual acuity. Finally, Pinheiro-Costa et al [26] demonstrated only an anatomical improvement in switched eyes.…”
Section: Resultsmentioning
confidence: 97%
“…Since Kumar et al reported that a significant improvement in visual acuity was not observed after initial three injections but it was occured 6 months later [23]. On the other hand, Homer et al did not declare a significant improvement in BCVA in their 24-month follow-up [24]. Most probably, BCVA improvement depends on multiple variables, such as initial IS/OS integrity, increasing age, increasing CMT, the presence of IRF and presence of PED [28].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation